2013
DOI: 10.1007/s00256-013-1640-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of chondromalacia isolated to the anterior margin of the lateral femoral condyle as a component of patellofemoral disease: observations at MR imaging

Abstract: A small percentage of patients with anterior knee pain have chondromalacia isolated to the anterior margin of the lateral femoral condyle. This was associated with a shallower femoral sulcus angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…According to Chan et al. (19), a small percentage of patients with anterior knee pain have chondromalacia isolated to the anterior margin of the lateral femoral condyle. This was associated with a shallower femoral sulcus angle.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chan et al. (19), a small percentage of patients with anterior knee pain have chondromalacia isolated to the anterior margin of the lateral femoral condyle. This was associated with a shallower femoral sulcus angle.…”
Section: Discussionmentioning
confidence: 99%
“…CP is the consequence of multiple factors including trauma to the knee, vascular insufficiency within the subchondral bone (5, 7), and misalignment of the extensor mechanism of the knee which could be caused by patella alta and infera, genu valgum, external tibial torsion, increased quadriceps (Q) angle, and deformities of the femoral condyle (8, 9). In order to investigate the etiology of CP and provide the theory basics for the early diagnosis and treatment of CP, some studies have evaluated the association of morphological features of the patellofemoral joint, such as lateral patellar tilt angle (LPTA), sulcus angle, trochlear depth, patella angle, lateral and medial patellar facet lengths, lateral-to-medial facet length ratio, interfacet angle, and anterior margin of the lateral femoral condyle, with CP (5, 10, 11). Also, in patients with patellofemoral joint osteoarthritis, patellar alignment, such as patellar height, sulcus angle and depth, lateral patellar displacement, and LPTA, was associated with cartilage lesions (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Endo et al [12] reported, there was not a statistically significant correlation between patellar chondromalacia and different measurements of patellar facet length and the inter-facet angle. Conversely, Thakkar et al [13] and Chan et al [14] concluded quantitative trochlear parameters could be reliably calculated on MRI. The literature on quantitative imaging is usually related to the patellar malalignment [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%